A retrospective investigation of orthognathic patients and functional needs - Borzabadi-Farahani Ali; Olkun Hatice Kübra; Eslamian Ladan; Eslamipour Faezeh (Sciendo, 2024)
The present study aimed to explore the malocclusion trends, sagittal skeletal discrepancies, and the index of orthognathic functional treatment need (IOFTN) scores in a sample of Iranian and Turkish orthognathic patients.